Infrastructure Services in Developing Countries : Access, Quality, Costs and Policy Reform - Briceño-Garmendia, Cecilia; Estache, Antonio; Shafik, Nemat (World Bank, Washington, D.C., 2013)
The authors review the evidence on the state of infrastructure in the developing world, emphasizing the investment needs and the emerging policy issues. While their assessment is seriously constrained by data gaps, they provide useful insights on the main challenges ahead, emphasizing that, in addition to the widely discussed access problems, the poorest also face major affordability and service quality issues which were not well addressed by the reforms of the 1990s. The authors make a case for a stronger commitment of the international community to generate the information needed to assess and monitor infrastructure needs and policies.